2022
DOI: 10.1155/2022/5827544
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related lncRNA Pairs and Construction and Validation of a New Prognostic Signature of Colon Cancer

Abstract: Background. More and more evidence has shown that immune-related long noncoding ribonucleic acid (irlncRNAs) is a potential prognostic factor for colon cancer. The relevant gene pair pattern can improve the sensitivity of the prognostic model. Therefore, our present study aimed to identify irlncRNA Pairs and construct and validate a new prognostic signature in colon cancer. Methods. We downloaded the expression matrix of mRNA and lncRNA of patients with colon cancer and their clinical information from the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Among them, all ARLs are crucial in many ways. For instance, there is an association between WWC2-AS2 and the prognosis of multiple cancer types, such as LUAD [ 34 ], cervical cancer [ 35 ] and colon cancer [ 36 ]. Due to this, WWC2-AS2 is believed to be crucial to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, all ARLs are crucial in many ways. For instance, there is an association between WWC2-AS2 and the prognosis of multiple cancer types, such as LUAD [ 34 ], cervical cancer [ 35 ] and colon cancer [ 36 ]. Due to this, WWC2-AS2 is believed to be crucial to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of WWC2-AS2 was corrected based on the in ltration level of immune cell subtypes [22] . Furthermore, Xu et al indicated that WWC2-AS2|AL355916.2, an immune-related long non-coding ribonucleic acid gene pair pattern in colon cancer, related to the survival outcome, clinicopathological characteristics of prognosis of colon cancer [23] . Thus, WWC2-AS2 could be used as a biomarker and therapeutic target for patients with PTC.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of immune-related lncRNAs has been found in various cancers. Currently, a prognostic model has been conducted based on eight immune-related lncRNAs pairs that can effectively predict the prognosis of patients with COAD ( 69 ). Here, we performed an in-depth analysis of the relationship between the risk model and the distribution of immune-infiltrating cells by ImmuCellAI.…”
Section: Discussionmentioning
confidence: 99%